2014
DOI: 10.7314/apjcp.2014.15.13.5343
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Six Randomized Control Trials of Chemotherapy Plus Anti-HER Monoclonal Antibody for Advanced Gastric and Gastroesophageal Cancer

Abstract: Background: A meta-analysis was performed to examine the benefit/risk ratio for the addition of anti-HER MoAbs to chemotherapy in patients with advanced gastric and gastroesophageal cancer from six randomized phase II/III trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
1
10
0
2
Order By: Relevance
“…HER2 expression has been found in gastric cancer. Inhibition of the HER2 receptor is a promising treatment target [4, 5] in breast cancers. Trastuzumab is a monoclonal antibody which specifically targets the HER2 protein by directly binding to the extracellular domain of the receptor.…”
Section: Introductionmentioning
confidence: 99%
“…HER2 expression has been found in gastric cancer. Inhibition of the HER2 receptor is a promising treatment target [4, 5] in breast cancers. Trastuzumab is a monoclonal antibody which specifically targets the HER2 protein by directly binding to the extracellular domain of the receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, trastuzumab has been reported to be effective in combination with first-line fluoropyrimidine and cisplatin therapy [33]. And the addition of trastuzumab to chemotherapy for gastric and gastroesophageal cancer significantly yielded survival benefits compared to other antibodies [34]. It was also reported that the association of trastuzumab with oxaliplatin and fluoropyrimidin could reduce the toxicity of therapy compared with the addition of fluoropyrimidin and cisplatin [35], which was consistent with the results of our NMA to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…El matuzumab es un anticuerpo monoclonal IgG1 humanizado contra HER1. En un ensayo aleatorizado de fase II realizado en pacientes con CG avanzado con sobreexpresión de HER1 se evaluó matuzumab + epirubicina + cisplatino + capecitabina como tratamiento de primera línea, y los resultados mostraron que la combinación de matuzumab con quimioterapia no mejora las tasas de sobrevida (Tabla 2); por lo tanto, el matuzumab no fue probado en ensayos de fase III 69,85 . El nimotuzumab es una IgG1 humanizada que ha demostrado eficacia sin toxicidad grave de la piel como la causada por otras terapias de unión a HER1; sin embargo, la sobrevida es similar a la observada con otros fármacos [70][71][72] (Tabla 2).…”
Section: Terapias Anti-her1unclassified
“…Un metaanálisis sugirió que las terapias basadas en anticuerpos monoclonales anti-HER1 para pacientes con CG resultan en tasas de sobrevida menores que las terapias anti-HER2. Sin embargo, la quimioterapia junto con la terapia dirigida anti-HER2 incrementa significativamente el riesgo de presentar diarrea, hipocalcemia, mucositis y exantema en comparación con la quimioterapia sola 85 . El trastuzumab emtansina (T-DM1) es un anticuerpo que combina trastuzumab y un inhibidor de microtú-bulos derivado de maitansina (DM1).…”
Section: Terapias Anti-her2unclassified